Added Effect of Yoga-Based Exercise Program on Balance and Fear of Fall in Chronic Post-Stroke Hemiparetics - Sailee Wakade (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background and aims The purpose of the study was to find out the added effect of Yoga-based exercise program alongwith conventional balance exercises on balance and fear of fall in chronic post-stroke hemiparetics. Balance in stroke patients is affected due to decrease in muscle strength, myotonus changes, sensory defect, abnormal posture reaction, and cognitive problems, and lack of central integration of somtosensory, vestibular and visual sensory inputs. Yoga has been known to improve strength in voluntary muscles and has an effect of somatosensory system. Methods An experimental study was carried out On 10 stroke patients picked through purposive random sampling in Talegoan Dabhade, 5 in the control group were given conventional balance exercises and 5 were given added Yoga exercises including asanas and pranayama(breathing exercises) for 4 weeks, 4 sessions per week. Pre and post outcome measures: POMA for balance and FES for fear of fall were taken. Results There was more improvement in POMA scores with a p-value of 0.01039 and FES scores with p-value 0.01739 in the experimental group which is statistically significant and hence favours the study.